2015
DOI: 10.1097/mop.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizures

Abstract: Routine diagnostic testing for simple febrile seizures is being discouraged, and clear evidence-based guidelines regarding complex febrile seizures are lacking. Thus, clinical acumen remains the most important tool for identifying children with seizures who are candidates for a more elaborate diagnostic evaluation. Similarly, evidence and guidelines regarding candidates for an emergent out-of-hospital diazepam treatment are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 66 publications
1
20
0
6
Order By: Relevance
“…Approximately, our patients were presented with complex febrile seizures, which is similar to some studies (9,10,26), but less than the reported rate of one third of all febrile seizures in other large studies (1,8). No specific viral infection was identified in these patients and all children in whom PCR assay for viruses or bacteria was positive had been presented with simple febrile seizures.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Approximately, our patients were presented with complex febrile seizures, which is similar to some studies (9,10,26), but less than the reported rate of one third of all febrile seizures in other large studies (1,8). No specific viral infection was identified in these patients and all children in whom PCR assay for viruses or bacteria was positive had been presented with simple febrile seizures.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 2% -5% of children have experienced at least one febrile seizure before they reach the age of 5 (1,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Классическим примером того, что эпилептический приступ не обязательно означает эпилепсию, являются фебрильные судороги. После приступа фебрильных судорог у значительного числа детей могут отмечаться эпилептиформные изменения на ЭЭГ, но это, как правило, не имеет прогностического значения и не свидетельствует о способности мозга продуцировать спонтанные приступы [5].…”
Section: Abstract: Misdiagnosis Of Epilepsy Children Non Epilepticunclassified
“…Таким образом, откладывание срока вакцинации до более старшего возраста ребенка не снижает риск развития ФС, т.е. нецелесообразно [10,11].…”
unclassified